Rapid Prototyping of 3D Biochips for Cell Motility Studies Using Two-Photon Polymerization - Sala, Federico; Ficorella, Carlotta; Martínez Vázquez, Rebeca; Eichholz, Hannah Marie; Käs, Josef A.; Osellame, Roberto (Frontiers in Bioengineering and Biotechnology, 2021)
The study of cellular migration dynamic and strategies plays a relevant role in the understanding of both physiological and pathological processes. An important example could be the link between cancer cell motility and tumor evolution into metastatic stage. These strategies could be strongly influenced by extracellular environment and the consequent mechanical constrains. In this framework, the possibility to study the behavior of single cells when subject to specific topological constrains could be an important tool in the hands of the biologists. Two-photon polymerization is a sub-micrometric additive manufacturing technique that allows the fabrication of 3D structures in biocompatible resins, enabling the realization of ad-hoc biochips for cell motility analyses, providing different types of mechanical stimuli. In our work, we present a new strategy for the realization of multilayer microfluidic lab-on-a-chip for cell motility study, that guarantees complete optical accessibility and the possibility to freely shape the migration area, to tailor it on the requirements of the specific cell type or experiment. The device includes a series of micro-constrictions that induce different types of mechanical stress on the cells during the migration. We show the realization of different possible geometries, in order to prove the versatility of the technique. As a proof of concept, we present the use of one of these devices for the study of the motility murine neuronal cancer cell under high physical confinement, highlighting their peculiar migration mechanisms.